Arkenstone - I: novel method for robustly capturing high specific energy outflows in cosmological simulations - Smith, Matthew C.; Fielding, Drummond B; Bryan, Greg L; Kim, Chang-Goo; Ostriker, Eve C.; Somerville, Rachel S; Stern, Jonathan; Su, Kung-Yi; Weinberger, Rainer; Hu, Chia-Yu; Forbes, John C.; Hernquist, Lars; et al. (Monthly notices of the Royal Astronomical Society, 2023)
Arkenstone is a new model for multiphase, stellar feedback-driven galactic winds designed for inclusion in coarse resolution cosmological simulations. In this first paper of a series, we describe the features that allow Arkenstone to properly treat high specific energy wind components and demonstrate them using idealized non-cosmological simulations of a galaxy with a realistic circumgalactic medium (CGM), using the arepo code. Hot, fast gas phases with low mass loadings are predicted to dominate the energy content of multiphase outflows. In order to treat the huge dynamic range of spatial scales involved in cosmological galaxy formation at feasible computational expense, cosmological volume simulations typically employ a Lagrangian code or else use adaptive mesh refinement with a quasi-Lagrangian refinement strategy. However, it is difficult to inject a high specific energy wind in a Lagrangian scheme without incurring artificial burstiness. Additionally, the low densities inherent to this type of flow result in poor spatial resolution. Arkenstone addresses these issues with a novel scheme for coupling energy into the transition region between the interstellar medium (ISM) and the CGM, while also providing refinement at the base of the wind. Without our improvements, we show that poor spatial resolution near the sonic point of a hot, fast outflow leads to an underestimation of gas acceleration as the wind propagates. We explore the different mechanisms by which low and high specific energy winds can regulate the star formation rate of galaxies. In future work, we will demonstrate other aspects of the Arkenstone model.
Gesehen am 08.07.2024